Effects of the daily heat load duration exceeding determined heat load thresholds on activity traits of lactating dairy cows. (October 2018) - Heinicke, Julia; Hoffmann, Gundula; Ammon, Christian; Amon, Barbara; Amon, Thomas
Abstract: In recent years, the problem of the welfare and heat load of dairy cows has become increasingly important in moderate climate zones. The objective of the present study was to determine heat load thresholds of average daily temperature-humidity index (THI) that lead to changes in different activity traits of lactating high-yielding dairy cows. Furthermore, we studied how the activity of the cows to heat load was influenced by the daily heat load duration which exceeded the heat load we had determined as threshold in our experiments. The study was conducted from June 2015 to May 2017 in a naturally ventilated dairy barn in Groß Kreutz, Germany. The climate was measured at several positions inside the barn, and the average THI was calculated every 10 min. The THI was used to define the dairy cows' heat load exposure. In addition, the activity of the cows was measured by pedometers, and different activity traits were recorded in the functional groups "resting behavior" and "locomotion behavior". The heat load thresholds determined by broken-stick models were 47 THI (standing bout duration, number of steps) as well as 67 THI (total lying/standing time, number of lying/standing bouts, lying bout duration). During the experimental period, the most reliable heat load threshold of 67 THI was exceeded from May to September for up to 480 h per month. The analysis model of each activity trait included the effect of the average daily THI values below and above the determined heat load threshold and the effect of the daily heat load duration exceeding the determined heat load threshold. The total lying/standing time and the number of steps showed significant changes related to increasing daily heat load duration. The effect of the daily heat load duration additionally intensified the effect of the average daily THI. Highlights: Early detection of heat load by monitoring the activity of dairy cows. Determined heat load threshold of 67 THI concerning activity changes of dairy cows. Heat load duration and intensity influenced the activity. Cows showed activity changes even after short heat load duration. Milk production level of cows influenced activity changes under heat load.